How a pandemic reshapes power patterns: a case study of electricity consumption in the Baltic countries during COVID-19 - Rajora, GopaL Lal; Sharma, Neha; Sanz Bobi, Miguel Ángel (My University, 2025)
In addition to the enormous loss of life caused by COVID-19, the pandemic produced issues in various sectors such as industrial, economic, tourism, healthcare, etc. One of the sectors that is likely to have been affected is energy systems.This study investigates how a global crisis such as a pandemic can reshape electricity consumption patterns. This paper explores the possible impact Baltic countries had due to the pandemic on electricity consumption.The analysis results indicate a significant impact on electricity consumption during the pandemic. Estonia, Latvia, and Lithuania saw a decrease in consumption by 2.74, 4.40, and 8.33, respectively, during the first lockdown period compared to the year 2019. However, leading to the new normal in 2021, the electricity consumption rebounded. In light of the global crisis, the dynamic electricity consumption pattern highlights how energy consumption can reflect societal shifts and could offer valuable insights to policymakers.